Textile Industry Wastewater Color Removal Using Lemna Minor L and Lemna Minuta L - Sivakumar, D; Anand, R; Saral, Asanammal (International Journal of Engineering and Technology, 2018)
The influence of various nutrient dosages, dilution ratios and pH values was evaluated with different contact time against colour removal from textile industry wastewater using Lemna minor L and Lemna minuta L.Â The optimum nutrient dosage, dilution ratio, and pH value was found to be 50 mg, 8 and 8 respectively. The maximum colour removal corresponding to the optimum process parameters value observed using Lemna minor L as 82.85 % and using Lemna minuta L as 89.5 %. Further, verification was done and showed that the maximum colour removal percentage from textile industry wastewater is lower than colour removal from an aqueous solution.Â The results of this study concluded that Lemna minuta L removed more colour than Lemna minor L and both were identified to reproduce the obtained optimum process parameters and for removing colour in a textile industry wastewater. Â Â